2015
DOI: 10.18768/ijaedu.09134
|View full text |Cite
|
Sign up to set email alerts
|

Lecturer Performances in Indonesia Higher Education System

Abstract: This paper is concern with Indonesia lecturers' performances on teaching and research activities. Particular attention is given to look at teaching and publication performances after a various compensation schemes introduced since 2008. The study began with developing the instruments integrating lecturer's characteristics and academic activities; i.e., including teaching, research, and time allocation. Around 54.000 of lecturers of higher system in Indonesia registered as permanent staffs of universities recei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 4 publications
1
11
0
2
Order By: Relevance
“…On the other hand, lecturers who have academic ranking professors and associate professors have dependents to produce scientific work. Puuska (2010) and Elfindri, Rustad, Nizam,& Dahrulsyah (2015) states that the productivity of professors is higher than in other positions.…”
Section: Factor Influencing Lecturer Research Performancesmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, lecturers who have academic ranking professors and associate professors have dependents to produce scientific work. Puuska (2010) and Elfindri, Rustad, Nizam,& Dahrulsyah (2015) states that the productivity of professors is higher than in other positions.…”
Section: Factor Influencing Lecturer Research Performancesmentioning
confidence: 99%
“…Countries where lecturers get their degrees are considered to influence the performance of publications because of differences in the quality of education of each country. Elfindri, Rustad, Nizam, & Dahrulsyah (2015) found that the international publications' productivity of lecturers who graduated from overseas universities was four to five much higher compared to the productivity of lecturers who graduated from domestic universities. One of the things that are complained by lecturers is the administrative burden that disturbs the focus of the lecturer in conducting research.…”
mentioning
confidence: 93%
“…Productivity is human desire and effort to always improve the quality of life and livelihood in all fields (Turban, McLean, & Wetherbe, 2001). Work productivity is the ability of employees to produce compared to the input used, an employee can be said to be productive when able to produce research work (Elfindri, Supriadi Rustad, Nizam, 2015). Characteristics of productivity are, first feel busy working until there is no time, both quality of work is a top priority in the work, third give the best effort in every job and fourth get maximum results with resource efficiency (L. W. Fry, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Scientific publications in reputable national and international journals, acting as a self-actualization medium for academics and researchers in the development of science internationally. However, according to (8) In general, the performance of lecturer scientific publications in Indonesia is far behind including the citation index compared to the scientific publications of lecturers in Southeast Asian countries. (8) said that based on the results of his research the scientific publications of lecturers will increase if there is a compensation policy on research performance.…”
Section: Introductionmentioning
confidence: 99%
“…However, according to (8) In general, the performance of lecturer scientific publications in Indonesia is far behind including the citation index compared to the scientific publications of lecturers in Southeast Asian countries. (8) said that based on the results of his research the scientific publications of lecturers will increase if there is a compensation policy on research performance. The size of a college's success is judged by how capable the universities produce high-quality products that are recognized by the public, both the scientific community and the general public.…”
Section: Introductionmentioning
confidence: 99%